Rising Income Inequality: Do Not Draw the Obvious Conclusions - Heiko Peters; Maya Volwahsen (Intereconomics, 2017)
Inequality is dominating the political debate in various countries still characterised by sluggish economic recovery and high unemployment. The drivers of higher income inequality since 1995 have been globalisation, technological change and migration. At the same time, these factors have had an undeniably positive impact on aggregate income. While populist parties advocate more nationalistic-oriented approaches, we argue that the appropriate policy response to this dilemma is to alleviate the social costs of globalisation rather than rejecting the aggregate economic benefit.
Keywords: 330